A comparative study of co-precipitation and sol-gel synthetic approaches to fabricate cerium-substituted Mg Al layered double hydroxides with luminescence properties - Smalenskaite, A. (2019)
Mg/Al/Ce layered double hydroxides (LDHs) intercalated with carbonate and hydroxide anions were synthesized using co-precipitation and sol-gel method. The obtained materials were characterized by thermogravimetric (TG) analysis, X-ray diffraction (XRD) analysis, fluorescence spectroscopy (FLS) and scanning electron microscopy (SEM). The chemical composition, microstructure and luminescent properties of these LDHs were investigated and discussed. The Ce3 + substitution effects were investigated in the Mg3Al1 − xCex LDHs by changing the Ce3 + concentration in the metal cation layers from 0.05 to 10 mol%. It was demonstrated, that luminescence properties of cerium-substituted LDHs depend on the morphological features of the host lattice.